The impact of experiential avoidance on the reduction of depression in treatment for borderline personality disorder - Berking, Matthias; Neacsiu, Andrada; Comtois, Katherine Anne; Linehan, Marsha Marie (Behaviour Research and Therapy, 2009)
Background: Reducing symptoms of depression is an important target in the treatment of borderline personality disorder (BPD). Although current treatments for BPD are effective in reducing depression, the average post-treatment level of depression remains high. Aim: To test whether experiential avoidance (EA) impedes the reduction of depression during treatment for BPD. Method: EA and depression were assessed in 81 clients at baseline and 4-month intervals during 1 year of therapy. Simple correlations, hierarchical linear modeling, and latent difference score models were used to investigate the association between self-reports of EA and both self-reports and observer-based ratings of depression. Results: EA was positively associated with greater severity of depression at all points of assessment, and changes in EA were positively associated with changes in depression. Moreover, EA significantly predicted less subsequent reduction in depression whereas no such effect was found for depression on subsequent EA. Conclusion: The findings are consistent with the hypothesis that EA impedes the reduction of depression in the treatment of BPD and should thus be considered an important treatment target. © 2009 Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Borderline personality disorder; Depression; Experiential avoidance; Outcome; Treatment